Usage Patterns of Telepsychology and Face-to-Face Psychotherapy: Clients’ Profiles and Perceptions - Sora, Beatriz; Nieto, Rubén; Montesano, Adrian; Armayones, Manuel (Frontiers in Psychology, 2022)
Background: Currently, most people who might need mental health care services do not receive them due to a number of reasons. Many of these reasons can be overcome by telepsychology, in other words, the use of ICT technologies for therapy (eg. phone, videoconferencing, and apps); given that it facilitates access to specialized interventions. In fact, telepsychology is currently offered as an active service in many psychotherapy centers. However, its usage, how it is perceived, and who uses it are still largely unknown. Objective: The aim of this study was (1) to determine if any pattern exists in the usage of telepsychology and face-to-face psychology, (2) to clarify people’s perception of telepsychology in terms of the advantages, barriers and efficacy of online psychotherapy, and (3) to examine usage patterns in terms of individual characteristics and identify patients’ profiles. Methods: An online survey was conducted on a convenience sample of 514 subjects recluted by using an online advertisement. The inclusion criteria were: (1) to be older than 18 years old and (2) to answer completely the questionnaire. Cluster analysis, Anovas and discriminant analysis were performed to test our research objectives. Results: Three usage clusters were found: (1) face-to-face psychotherapy (57%; n=292); (2) non-therapy (36.8%; n=189); and (3) combined face-to-face psychotherapy and telepsychology (6.4%; n=33). In addition, the perception of telepsychology varied among usage clusters, but a common perception emerged about the main telepsychology advantages, barriers and efficacy. Finally, the results showed that personal characteristics differentiated people in each of these clusters. Conclusions: The most common form of access to psychotherapy is the face-to-face form but the second way of delivery was a combination between face to face and online psychotherapy (research objective 1). People who combine face to face with online psychotherapy perceives this last as more efficient and with less barriers to access (research objective 2). Finally, some characteristic as eHealth experience and sociodemographic variables can help to identify people that will attend telepsychology initiatives (research objective 3). These clusters provide insight into opportunities for face-to-face and online patient engagement strategies.